Protein-driven RNA nanostructured devices that function in vitro and control mammalian cell fate - Tomonori Shibata (Nature Portfolio, 2017)
Nucleic acid nanotechnology has great potential for future therapeutic applications. Here the authors build protein-driven RNA nanostructures that can function within mammalian cells and regulate the cell fate.